Evaluación de la toxicidad del cromo en Tecoma stans (cholán) - Zapata Padilla, Daniela Nicole (2019)
Currently, industrial discharges to water bodies have brought negative impacts to the environment, generating alterations in the quality of ecosystems and human health. One of these cases is the sub-basin of the Cutuchi River, located between Laso and Latacunga, in these areas there are tanning industries which apply trivalent chromium salts for their processes. This element causes harmful effects on biota and human health, for this reason the objective of the present study is to evaluate the toxicity of chromium on Tecoma stans (Cholán), both in the germination of seeds and in the development of seedlings. In the case of the seeds, 5 repetitions per treatment were performed using 10 seeds per repetition, for the seedlings 15 repetitions per treatment was used. Synthetic water was prepared at different concentrations of Cr III, the first of 4 mg / L, the second of 17.5 mg / L and the third was 35 mg / L, the control treatments were calm water and river water Cutuchi These five treatments were applied to the seeds for 8 days and in the seedlings for 2 months. It was determined that at a higher concentration of Cr III, lower germination and root growth, on the contrary, control treatments contributed positively to both parameters. On the other hand, the seedlings followed the same trend since there were malformations in the leaves, abnormal ramifications and the root volume decreased; the control treatments did not significantly affect the development of the plants.